A STUDY OF BURNOUT AMONG PRIMARY SCHOOL TEACHERS - Raj, Tilak (THE PRIMARY TEACHER, 2010)
This paper is aimed at investigating the burnout among primary school teachers of Solan district of Himachal Pradesh. A sample of 120 teachers, both male and female, was drawn from 40 government primary schools. Data were collected using a questionnaire. Mean, SD and t-test were employed for analysis of the data. The results revealed that female teachers are more prone to burnout than male teachers. It was observed that urban teachers show more burnout than rural teachers and highly qualified teachers have more burnout than that of their low qualified counterparts.The results of the study further explore that burnout exists more among low experienced teachers than their high experienced counterparts.